Strategic Analysis of Internal and External Coordination of West Sumatra Halal Task Force using SWOT Methodology - Rahmi, Vethria; Dewi, Rahmi Surya; Darwis, Yuliandre (Fakultas Ilmu Sosial dan Ilmu Poliitik Universitas Ichsan Gorontalo, 2025)
Fokus penelitian ini tentang strategi koordinasi Satgas Halal Sumatera Barat. Tujuannya, untuk mengetahui bagaimana analisis koordinasi internal (vertikal/horizontal) dan eksternal (diagonal) Satgas Halal Sumbar. Signifikansi penelitian ini adalah pentingnya strategi koordinasi menurut kendali organisasi Tompkins dan Cheney (1987) yang sederhana untuk diterapkan bagi Satgas Halal sumbar. Relevansinya adalah Satgas Halal Sumbar sedang memiliki kelemahan struktur organisasi, minim SDM Ahli, minim pelatihan koordinasi dan tidak diberi kewenangan anggaran. Maka dibutuhkan 4 konsep kendali unobstrusive, sosialisasi, identifikasi organisasi dan kendali konsertif dalam pelaksanaan koordinasinya. Metode yang digunakan adalah kualitatif dengan pendekatan analisis SWOT yang melibatkan pengumpulan data primer dan sekunder. Analisis SWOT ini krusial untuk mengetahui hasil evaluasi dalam pengembangan perencanaan strategis Satgas Halal Sumbar. Hasil penelitian menunjukkan bahwa Satgas Halal Sumbar belum optimal dalam mengarahkan perilaku anggotanya untuk meningkatkan level kualitas koordinasinya. BPJPH dan satgas Halal Sumbar masih dominan menerapkan pola komunikasi organisasi yang sentralistik. Sedangkan penerapan kendali organisasi Tompskins & Cheney (1987) masih minim. Implikasinya, Satgas Halal masih belum dapat bertindak otonom dalam menjalankan fungsi koordinasi, edukasi, pengawasan dan administrasi. Konsekuensinya, Satgas Halal Sumbar masih kurang menerapkan komunikasi interpersonal yang efektif dalam koordinasinya. Hasil analisis SWOT menunjukkan kelemahan strategi koordinasi Satgas Halal Sumbar lebih dominan dibandingkan dengan kekuatan dan peluangnya. The focus of this research is on the coordination strategy of the West Sumatra Halal Task Force. The aim is to find out how the internal (vertical/horizontal) and external (diagonal) coordination analysis of the West Sumatra Halal Task Force is carried out. The significance of this research is the importance of coordination strategies according to Tompkins and Cheney (1987) organizational control which are simple to apply for the West Sumatra Halal Task Force. The relevance is that the West Sumatra Halal Task Force currently has a weak organizational structure, minimal expert human resources, minimal coordination training and is not given budgetary authority. So four concepts of unobtrusive control, socialization, organizational identification and concertive control are needed in the implementation of coordination. The method used is qualitative with a SWOT analysis approach which involves collecting primary and secondary data. This SWOT analysis is crucial for knowing the results of the evaluation in developing strategic planning for the West Sumatra Halal Task Force. The research results show that the West Sumatra Halal Task Force has not been optimal in directing the behavior of its members to increase the level of quality of coordination. BPJPH and the West Sumatra Halal task force still predominantly apply centralized organizational communication patterns. Meanwhile, the implementation of organizational control by Tompskins & Cheney (1987) is still minimal. The implication is that the Halal Task Force is still unable to act autonomously in carrying out coordination, education, supervision and administration functions. As a consequence, the West Sumatra Halal Task Force still lacks effective interpersonal communication in its coordination. The results of the SWOT analysis show that the weaknesses of the West Sumatra Halal Task Force's coordination strategy are more dominant than its strengths and opportunities.